Profil Mahasiswa Program Studi Pendidikan Biologi FKIP UMS dalam Melaksanakan Penelitian Skripsi Tahun 2013 - Agustina, Nikmah; , Dra.Hariyatmi,M.Si (2016)
Undergraduate thesis is one type of research paper in collage whom are doing by student university in undergraduate. Purpose of this study was to determine the profile of Biology Education Student this UMS in conducting undergraduate thesis in 2013. The method of the research is qualitative descriptive using paper documentation.The strategie was using include models to explain the survey and obtain the data, so the results can describe fully and indepth the various phenomena that happen. Data analysis used descriptive qualitative. Based on the results of the study, the selected areas of research students are education (53.7%), applied (24.7%), and pure (21.6%).The selected student research approach is quantitative (48.4%), qualitative (27.4%), as well as the combination (24.2%). The research method selected students experiment (73.2%), PTK (20,0%), descriptive (4.2%),ex post facto (1,6%),as well as an VES and exploration (0,5%) respectively. Study schools are being focused in educational research, junior high school (82,4%), senior high school (9,8%), university and vocantional high school (3,9%) respectively. Thus, it can be concluded that the students of Biology Education FKIP UMS who graduated in 2013 had a tendency to choose the field of education research, quantitative research approach, the experimental method, as well as the junior high school level are being focused in educational research.